The influence of manufacturing technology on the properties of layered composites with polyester–glass recyclate additive. Issue 1 (February 2020) - Kyzioł, Lesław; Panasiuk, Katarzyna; Barcikowski, Michał; Hajdukiewicz, Grzegorz
The article describes the technologies of recycling polyester–glass waste and the influence of manufacturing technology on the properties of layered composites with polyester–glass recyclate additive. Milled polyester–glass waste was used as the recyclate. Polyester–glass composites with a specific content of recyclate were manufactured by means of manual laminating and vacuum bagging. The influence of the recyclate content and manufacturing method on the mechanical properties of composites was determined with the aid of specimens exposed to static tensile testing. Test results indicated that the composite without recyclate additive manufactured by means of vacuum bagging exhibits higher strength properties than the same composite manufactured by means of manual laminating. Additionally, its plasticity is much higher than that of the composite manufactured by means of manual laminating. The tests indicated that the tensile properties of the composite are, essentially, influenced by the content of recyclate (apart from the manufacturing method). Adding recyclate to the manufactured composite in the amount of 10% and 20% causes a significant decrease in its tensile properties in relation to the composite without the recyclate.